Boynton Lindsay, The Elizabethan Militia 1558 - 1638 - Izdebski, Hubert (Czasopismo Prawno-Historyczne, 1970)
Recenzja: Lindsay Boynton, The Elizabethan Militia 1558 - 1638, London—Toronto, 1967, s. XVII + 334, Studies in Political History.